Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2021
DOI: 10.1007/s42399-021-00851-1
|View full text |Cite
|
Sign up to set email alerts
|

Diabetes Mellitus and Hypertension Increase Risk of Death in Novel Corona Virus Patients Irrespective of Age: a Prospective Observational Study of Co-morbidities and COVID-19 from India

Abstract: Elderly people and people with co-morbidities have emerged as the most vulnerable group at risk of developing complications and succumbing to novel coronavirus (COVID-19) infection. We recorded the baseline demographic profile, baseline clinical and laboratory parameters, and prevalence of various co-morbidities and their effect on the prognosis of COVID-19 cases. We conducted a prospective observational study and analyzed baseline clinical and laboratory parameters and co-morbidities and their effect on sever… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(19 citation statements)
references
References 12 publications
3
16
0
Order By: Relevance
“…Abate et al (2021) conducted a systematic review and found a 48% prevalence of comorbidities in hospitalized patients, with diabetes mellitus (48%) predominating, followed by hypertension and cardiovascular diseases (15%) [ 38 ]. Among the main risk factors listed in this study were chronic cardiovascular disease, diabetes mellitus and obesity, which have also been found in other studies [ 39 , 40 , 41 , 42 ]. Our findings indicated the presence of a risk factor in 73% of deaths, but these results can be explained by the fact that we only examined the number of deaths.…”
Section: Discussionsupporting
confidence: 87%
“…Abate et al (2021) conducted a systematic review and found a 48% prevalence of comorbidities in hospitalized patients, with diabetes mellitus (48%) predominating, followed by hypertension and cardiovascular diseases (15%) [ 38 ]. Among the main risk factors listed in this study were chronic cardiovascular disease, diabetes mellitus and obesity, which have also been found in other studies [ 39 , 40 , 41 , 42 ]. Our findings indicated the presence of a risk factor in 73% of deaths, but these results can be explained by the fact that we only examined the number of deaths.…”
Section: Discussionsupporting
confidence: 87%
“…Park et al analyzed the Korean population and found both diabetes and hypertension to be risk factors for death in the course of COVID-19 [ 34 ]. The same results were achieved by Gupta et al among Indian patients [ 35 ]. Chen et al demonstrated only ischemic heart disease and cerebrovascular disease to be independently associated with high mortality in Chinese patients [ 36 ].…”
Section: Discussionsupporting
confidence: 85%
“…Moreover it does not take into account patients with ARF due to Covid-19 admitted directly from ER to ICU; this could explain the relatively low outcome failure and mortality ratio seen in our study (respectively 32.4% and 16.6%). However, outcome failure, as defined by need for invasive mechanical ventilation and/or death, was online with previous literature describing patients outside ICU setting [ [29][30][31][32],]. Outcome failure results could be affected to the decision to start IMV according to PF value of the patient (for example a rapid decline of P/F), so that this could represent a bias of this study, while mortality is independent.…”
Section: Discussionmentioning
confidence: 91%
“…In previous studies the average prevalence of outcome failure and mortality, respectively, were 43,7% and 19,6%. [ [29][30][31][32],].…”
Section: Methodsmentioning
confidence: 99%